COVID-19 presenting as intussusception in infants: A case report with literature review - Athamnah, Mohammad N. (J Pediatr Surg Case Rep, 2021)
The novel Corona virus disease 2019 (COVID-19) first presented in Wuhan, China. The virus was able to spread throughout the world, causing a global health crisis. The virus spread widely in Jordan after a wedding party held in northern Jordan. In most cases of COVID-19 infection, respiratory symptoms are predominant. However, in rare cases the disease may present with non-respiratory symptoms. The presentation of COVID-19 as a case of intussusception in children is a strange and rare phenomenon. We present here a case of a two-and-a-half month old male baby who was brought to hospital due to fever, frequent vomiting, dehydration and blood in stool. He was diagnosed as intussusception. The child was tested for corona due to the large societal spread of the virus and because he was near his mother, who was suffering from symptoms similar to corona or seasonal flu (she did not conduct a corona test). Patient was treated without surgery and recovered quickly. The COVID-19 infection was without respiratory symptoms, and there was no need for the child to remain in hospital after treatment of intussusception. The relationship between viruses, mesenteric lymphoid hyperplasia, and intussusception is a confirmed relation. ACE2 is the key receptor required for SARA-COV-2 to enter the host cells. ACE2 has been also found in the brush border of the intestinal mucosa, as well as it is a key inflammatory regulator in the intestine. This may suggest that SARSA-COV-2 could invade the respiratory tract as well as gastrointestinal tract or both. Few case reports documented the presentation of COVID-19 as intussusception in children. In the light of the wide-spread of corona virus, performing COVID-19 tests for children with intussusception can help linking the two entities. Development of gastrointestinal symptoms in COVID-19 positive children should raise concern about the development of intussusception.